Analisis Perbandingan Ahp–Topsis Dan Moora Untuk Penilaian Kinerja Karyawan - Tengku Eky Fatdhillah Sugiono; Dina Agus Mardiani; Yustian Servanda (Nolsatu Publisher, 2026)
Employee performance evaluation is a crucial aspect in supporting objective and measurable managerial decision-making. However, in practice, performance assessment is often still subjective and not fully supported by systematic analytical methods. This study aims to analyze and compare the combined Analytical Hierarchy Process and Technique for Order Preference by Similarity to Ideal Solution (AHP–TOPSIS) method with the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method in a Decision Support System for employee performance evaluation at PT Classics Prima Sejahtera. This research applies a quantitative approach using a case study method, where data are collected through observation, interviews, and performance assessment questionnaires. AHP is employed to determine the weights of evaluation criteria based on their level of importance, while TOPSIS and MOORA are used to rank employee performance. The results indicate that both methods are capable of producing objective employee rankings; however, differences in ranking order occur due to the distinct computational characteristics of each method. The AHP–TOPSIS method demonstrates advantages in terms of accuracy in criteria weighting, whereas MOORA offers a simpler and more efficient calculation process. This study concludes that both methods can be effectively applied as decision support tools, with the selection of methods depending on the needs and complexity of decision-making within the organization.